Composite gel electrolyte as well as preparation method and application thereof
By using composite gel electrolytes in lithium batteries, the modified nanoparticles react with organic precursors to generate composite polymers, the problems of flammability of traditional liquid electrolytes and poor uniformity of gel electrolytes are solved, and the performance of lithium secondary batteries is achieved. Improvement and security.
Patent Information
- Application Number
- CN202310678285.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-17
AI Technical Summary
The liquid electrolytes of traditional lithium batteries are flammable and difficult to be evenly distributed in large-sized batteries, resulting in insufficient performance and safety hazards. The existing gel electrolytes have poor wetting and uniformity in large-sized batteries.
Compound gel electrolyte is used, consisting of electrolyte salts, solvents and modified nanoparticles. The modified nanoparticles react with organic precursors to generate composite polymers, which are uniformly dispersed in the battery to ensure uniform distribution of the electrolyte and low viscosity wetting.
The uniform distribution of gel electrolytes in lithium secondary batteries is achieved, which improves battery performance, especially in large-sized batteries, and enhances safety and performance stability.
Smart Images

Figure CN119153769A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium secondary battery preparation, and relates to a composite gel electrolyte, a lithium secondary battery, and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have achieved great success in the commercialization of the consumer electronics industry due to their light weight, high energy density, good cycle performance and rate performance. With the rise of electric vehicles, the pursuit of vehicle range and service life has led to the continuous improvement of lithium-ion batteries' energy density and cycle life. However, the liquid electrolyte of traditional lithium batteries uses flammable organic solvents, which have the risk of leakage and flammability, limiting the improvement of battery performance.
[0003] Compared with liquid electrolytes, gel electrolytes have the advantages of no leakage, good stability, high safety, and strong plasticity. However, because the gel electrolyte itself has a high viscosity, its wettability and uniformity are poor in large-size batteries. Chinese patent application CN104966848A discloses a gel electrolyte, which is made of polyvinyl alcohol, anhydride and isocyanate as raw materials, and is obtained by chemical reaction in the presence of an initiator, a cross-linking agent, a lithium salt and an organic solvent. However, all the raw materials inevitably begin to react when mixed, causing the overall viscosity to increase, making it difficult to distribute evenly in the battery. Other methods such as radiation method to form polymerized electrolytes are also difficult to ensure the consistency of reaction conditions and the uniformity of electrolytes in large-size and thick batteries, which has an adverse effect on the overall performance of the battery. Summary of the invention
[0004] In view of the above problems existing in the existing gel electrolyte, the present invention provides a composite gel electrolyte to meet the requirements of lithium battery use. The composite gel electrolyte can achieve uniform distribution of the gel electrolyte in the lithium secondary battery and improve the performance of the lithium secondary battery.
[0005] The technical scheme for realizing the present invention is: a composite gel electrolyte, which is composed of electrolyte salt, solvent and composite polymer. The mass fraction of electrolyte salt in the nano composite gel electrolyte is 15-30%, the mass fraction of solvent is 50-80% and the mass fraction of composite polymer is 5-20%.
[0006] The composite polymer in the composite gel electrolyte is generated by the reaction of modified nanoparticles and organic precursors, wherein the mass ratio of the modified nanoparticles to the organic precursor is 2:1-1:4.
[0007] The modified nanoparticles are at least one of Al2O3, nano-SiO2, nano-ZnO, nano-SnO2 or nano-TiO2, and the size of the modified nanoparticles is 5-500nm.
[0008] The modified nanoparticles are nanoparticles modified with curing groups, wherein the curing groups include but are not limited to amino groups and carboxyl groups.
[0009] The organic precursor has a group that can react with the curing group of the modified nanoparticles. The organic precursor includes but is not limited to an epoxy group.
[0010] The electrolyte salt in the composite gel electrolyte is one or more of LiClO4, LiPF6, LiOH, LiTFSI, LiFSI or LiFNFSI; the organic solvent is one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate or methyl propyl carbonate.
[0011] A lithium secondary battery prepared with a composite gel electrolyte comprises a positive electrode sheet, a negative electrode sheet, a separator and a composite gel electrolyte. The composite gel electrolyte fills the entire battery space, including the positive electrode sheet, the negative electrode sheet and the separator.
[0012] The positive electrode sheet can be obtained by preparing a slurry of positive electrode active material, conductive agent, binder and modified nanoparticles in a solvent and coating the slurry on aluminum foil. The positive electrode active material can be a nickel-cobalt-aluminum ternary material, a nickel-cobalt-manganese ternary material, lithium cobaltate, lithium nickelate, lithium manganate, lithium iron phosphate or phosphorus, sulfur and lithium polysulfide.
[0013] The positive electrode sheet can also be obtained by dry mixing, fibrillating, and rolling the positive electrode active material, conductive agent, fiber binder, and modified nanoparticles and then compounding them with aluminum foil. The positive electrode active material can be a nickel-cobalt-aluminum ternary material, a nickel-cobalt-manganese ternary material, lithium cobaltate, lithium nickelate, lithium manganate, lithium iron phosphate, or phosphorus, sulfur, or lithium polysulfide.
[0014] The negative electrode sheet can be obtained by preparing a slurry of negative electrode active material, conductive agent, binder and modified nanoparticles in a solvent and coating the slurry on copper foil. The negative electrode active material can be graphite, silicon, silicon dioxide and other materials.
[0015] The negative electrode sheet can also be obtained by dry mixing, fibrillating, and rolling the negative electrode active material, conductive agent, fiber binder, and modified nanoparticles and then compounding them with copper foil. The negative electrode active material can be graphite, silicon, silicon oxide, and other materials.
[0016] The separator can be a porous PE film, a porous PP / PE / PP composite film, an inorganic solid electrolyte membrane or a polymer solid electrolyte membrane.
[0017] The lithium secondary battery preparation method comprises the following steps:
[0018] (a) When preparing positive and negative electrodes, the modified nanoparticles are mixed into the positive and negative electrodes of the lithium secondary battery by a dry method or a wet method, wherein the modified nanoparticles account for 1-10% of the mass fraction of the positive electrode and the negative electrode.
[0019] (b) adding the modified nanoparticles into an organic solvent and stirring the mixture to form a colloidal slurry.
[0020] (c) coating the colloidal slurry prepared in step (b) on both sides of the diaphragm, and vacuum drying to obtain a diaphragm coated with a nanoparticle coating;
[0021] (d) mixing the organic precursor into the lithium secondary battery electrolyte and mixing them evenly, wherein the mass fraction of the organic precursor is 1-20%.
[0022] (e) sequentially assembling and packaging the positive electrode sheet prepared in step (a), the separator coated with the nanoparticle coating prepared in step (c), and the negative electrode sheet prepared in step (a) into a battery cell;
[0023] (f) injecting the electrolyte containing the organic precursor prepared in step (d) into the battery cell, and then encapsulating the battery cell after soaking the entire battery cell.
[0024] (g) Waiting for the organic precursor and nanoparticles to react by standing or heating to eventually form a gel electrolyte battery.
[0025] The beneficial effects of the present invention are as follows: the composite gel electrolyte lithium secondary battery of the present invention uniformly disperses the modified nanoparticles necessary for the reaction in the positive electrode, negative electrode and diaphragm of the battery. The organic precursor can smoothly infiltrate the pole piece and diaphragm of the battery through the low-viscosity electrolyte. This method can effectively control the uniform formation of gel in the battery, thereby improving the performance of the battery. The effect is more prominent in large-sized batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 is a structural diagram of a lithium battery of the present invention;
[0028] Figure 2 is a capacity cycle performance diagram of the lithium battery of Example 1;
[0029] In the figure, 101 is a positive electrode current collector, 102 is a composite positive electrode, 103 is a negative electrode current collector, 104 is a composite negative electrode, 105 is a nano coating, 106 is a separator, and 107 is a gel electrolyte. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A lithium secondary battery, the structure of which comprises:
[0033] (1) A positive electrode sheet, which includes a positive electrode current collector 101 and a composite positive electrode 102;
[0034] (2) A negative electrode sheet, which includes a negative electrode current collector 103 and a composite negative electrode 104;
[0035] (3) diaphragm 106;
[0036] (4) Nanoparticle coating 105 , applied on both sides of the diaphragm 106 .
[0037] (5) Composite gel electrolyte 107, filling the entire lithium battery space.
[0038] The preparation method of lithium secondary battery is as follows:
[0039] Composite positive electrode preparation:
[0040] (1) Amino-modified SiO2 nanoparticles were mixed with lithium iron phosphate cathode, conductive carbon black, PVDF, and solvent NMP in a mass ratio of 2:88:5:5:100, and a composite cathode slurry was prepared using a planetary mixer.
[0041] (2) The composite positive electrode slurry in (1) is coated on aluminum foil, dried with air at 120 degrees, and then rolled and cut to obtain positive electrode sheets 101-102; the surface density is 15.0 mg / cm 2 , compacted density 2.0g / cm 3 .
[0042] Composite negative electrode sheet preparation:
[0043] (3) Amino-modified SiO2 nanoparticles were mixed with graphite anode, conductive carbon black, LA136D, and solvent water in a mass ratio of 2:88:5:5:100, and a composite anode slurry was prepared using a planetary mixer.
[0044] (4) The composite negative electrode slurry in (3) is coated on a copper foil, dried at 100 degrees by air blast, and then rolled and cut to obtain negative electrode sheets 103-104; the surface density is 8.6 mg / cm 2 , compacted density 1.6g / cm 3 .
[0045] Coated diaphragm preparation:
[0046] (5) Dispersing amino-modified SiO2 nanoparticles and CMC in solvent water at a mass ratio of 10:1, and stirring thoroughly to obtain a coating slurry.
[0047] (6) Coating the coating slurry prepared in step (5) on both sides of the porous PE diaphragm and drying it at 80 degrees with a forced air blower to obtain a coated diaphragm. The coating thickness on each side of the diaphragm is about 2 μm;
[0048] (7) Assemble the battery cell in the order of composite positive electrode sheet, coated separator, and composite negative electrode sheet.
[0049] (8) The organic precursor and the electrolyte are evenly mixed in a mass ratio of 10:100 and injected into the battery cell.
[0050] (9) The battery cell is placed in a vacuum chamber to allow the liquid to be evenly distributed in the battery cell, and then the battery cell is packaged to obtain a gel electrolyte battery.
[0051] The basic steps of Examples 2 to 5 are the same as those of Example 1, except for the positive electrode material, nanoparticle type, electrode nanoparticle mass fraction, negative electrode material, and the types of lithium salt and organic solvent in the electrolyte. See the table below for details:
[0052] Table 1
[0053]
[0054]
[0055] Example 6
[0056] The preparation method of lithium secondary battery is as follows:
[0057] Composite positive electrode preparation:
[0058] (1) Amino-modified SiO2 nanoparticles, lithium iron phosphate positive electrode, conductive carbon black, and PTFE were fully dry-mixed in a V-shaped mixer at a mass ratio of 2:88:5:5. The mixed powder was extruded through a screw extruder to obtain a surface density of 15.0 mg / cm 2 , compacted density 2.4g / cm 3 A composite positive electrode 102.
[0059] (2) The composite positive electrode in (1) is hot-pressed with aluminum foil and cut to obtain composite positive electrode sheets 101-102.
[0060] Composite negative electrode sheet preparation:
[0061] (3) Amino-modified SiO2 nanoparticles were thoroughly dry-mixed with graphite anode, conductive carbon black, and PTFE in a mass ratio of 2:88:5:5 using a V-shaped mixer. The mixed powder was extruded through a screw extruder to obtain a surface density of 8.5 mg / cm 2 , compacted density 1.8g / cm 3 A composite negative electrode 104 is provided.
[0062] (4) The composite negative electrode in (3) is hot-pressed with copper foil and cut to obtain composite positive electrode sheets 103-104.
[0063] Coated diaphragm preparation:
[0064] (10) Disperse the amino-modified SiO2 nanoparticles and CMC in solvent water at a mass ratio of 10:1 and stir thoroughly to obtain a coating slurry.
[0065] (11) Coating the coating slurry prepared in step (5) on both sides of a porous PE diaphragm and drying it at 80 degrees with a forced air blower to obtain a coated diaphragm. The coating thickness on each side of the diaphragm is about 2 μm;
[0066] (12) Assemble the battery cell in the order of composite positive electrode sheet, coated separator, and composite negative electrode sheet.
[0067] (13) The organic precursor and the electrolyte are evenly mixed in a mass ratio of 10:100 and injected into the battery cell.
[0068] (14) The battery cell is placed in a vacuum chamber to allow the liquid to be evenly distributed in the battery cell, and then the battery cell is packaged to obtain a gel electrolyte battery.
[0069] The basic steps of Examples 7 to 10 are the same as those of Example 6, except for the positive electrode material, nanoparticle type, negative electrode material, electrode nanoparticle ratio, separator type, separator coating thickness, and types of lithium salt and organic solvent in the electrolyte. See the table below for details:
[0070] Table 2
[0071]
[0072] The above example was subjected to charge and discharge tests to calculate the discharge capacity retention rate, with a charge and discharge rate of 0.5C.
[0073] Table 3
[0074] Example 1 2 6 7 Number of cycles with discharge capacity < 80% 2150 2080 1734 1780 The number of cycles when the discharge capacity of the control group was <80% 1900 1910 1439 1456
[0075] Table 3 shows the number of charge and discharge cycles when the capacity retention rate of Examples 1, 2, 6, and 7 is lower than 80%, with the corresponding pure electrolyte as the control group.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite gel electrolyte, characterized in that: The composite gel electrolyte is composed of electrolyte salt, solvent and composite polymer. The mass fraction of electrolyte salt in the nano composite gel electrolyte is 15-30%, the mass fraction of solvent is 50-80% and the mass fraction of composite polymer is 5-20%.
2. The composite gel electrolyte according to claim 1, characterized in that: The composite polymer is generated by the reaction of modified nanoparticles and organic precursors, wherein the mass ratio of the modified nanoparticles to the organic precursors is 2:1-1:
4.
3. The composite polymer according to claim 2, characterized in that The modified nanoparticles are at least one of Al2O3, nano-SiO2, nano-ZnO, nano-SnO2 or nano-TiO2, and the size of the modified nanoparticles is 5-500nm.
4. The composite polymer according to claim 2, characterized in that The modified nanoparticles are nanoparticles modified with curing groups, wherein the curing groups include but are not limited to amino groups and carboxyl groups.
5. The composite polymer according to claim 2, characterized in that The organic precursor has a group that can react with the curing group in claim 4, and the organic precursor includes but is not limited to an epoxy group.
6. The composite gel electrolyte according to claim 1, characterized in that: The electrolyte salt is one or more of LiClO4, LiPF6, LiOH, LiTFSI, LiFSI or LiFNFSI; the organic solvent is one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate or methyl propyl carbonate.
7. A lithium secondary battery prepared using the composite gel electrolyte according to any one of claims 1 to 5, characterized in that: The lithium secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and a composite gel electrolyte, wherein the composite gel electrolyte fills the entire battery space, including the positive electrode sheet, the negative electrode sheet and the separator.
8. The method for preparing a lithium secondary battery according to claim 7, characterized in that: Here are the steps: (a) When preparing positive and negative electrode sheets, the modified nanoparticles are mixed into the positive and negative electrode sheets of the lithium secondary battery by a dry method or a wet method, wherein the modified nanoparticles account for 1-10% by mass of the positive electrode and the negative electrode; (b) adding the modified nanoparticles into an organic solvent and stirring the mixture to form a colloidal slurry; (c) coating the colloidal slurry prepared in step (b) on both sides of the diaphragm, and vacuum drying to obtain a diaphragm coated with a nanoparticle coating; (d) mixing the organic precursor into the lithium secondary battery electrolyte and mixing evenly, wherein the mass fraction of the organic precursor is 1-20%; (e) sequentially assembling and packaging the positive electrode sheet prepared in step (a), the separator coated with the nanoparticle coating prepared in step (c), and the negative electrode sheet prepared in step (a) into a battery cell; (f) injecting the electrolyte containing the organic precursor prepared in step (d) into the battery cell, encapsulating the battery cell after soaking the entire battery cell; (g) Waiting for the organic precursor and nanoparticles to react by standing or heating to eventually form a gel electrolyte battery.
